Pemberdayaan Kader Sigap Stroke Berbasis Community Health Nursing untuk Meningkatkan Kapasitas Deteksi Dini dan Respons Awal Stroke di Desa Antasan Senor Ilir - Bernadetta Germia Aridamayanti; Muhammad Iqbal Qushoyyi; Maya Raaida Latifah; Khusnul Khotimah; Renia Nor Azzahra; Isma Azizah (Jurnal Medika: Medika, 2026)
Stroke was one of the leading causes of mortality and long-term disability, requiring early detection and prompt response to reduce complications. Antasan Senor Ilir Village experienced a high burden of stroke accompanied by limited community awareness and inadequate health cadres' capacity to recognize early stroke symptoms. This community service program aimed to improve the capacity of health cadres in early stroke detection and initial response through a Community Health Nursing-based empowerment approach. The program was conducted on 27–28 June 2026 in Antasan Senor Ilir Village, Banjar Regency, South Kalimantan, involving 25 health cadres from the Family Welfare Movement (PKK) and the Integrated Non-Communicable Disease Post (Posbindu PTM). The intervention consisted of community education, training, demonstrations, FAST (Face, Arm, Speech, Time) simulations, and mentoring. Program outcomes were evaluated using pre-tests, post-tests, and direct observation of participants' practical skills. The findings demonstrated that the proportion of cadres with good knowledge increased from 8.0% to 84.0%. The mean knowledge score improved from 61.84 to 88.72, accompanied by substantial improvements in early stroke detection and initial response skills across all FAST components. Participant attendance exceeded the initial target by reaching 125%, and the program also initiated the establishment of the Stroke Response Cadre Team at the village level. The Community Health Nursing-based empowerment approach effectively improved the knowledge and practical skills of health cadres in supporting community-based stroke prevention, early detection, and initial response.